APPLICATIONS OF NOVEL SILICON AND ALUMINUM BASED SUBSTRATES FOR THE SURFACE-ENHANCED SPECTROSCOPIES: SERS AND SEF - Sultangaziyev, Alisher (Nazarbayev University School of Sciences and Humanities, 2021)
This Master’s thesis investigates the applicability of non-traditional substrates for surface-enhanced Raman spectroscopy and surface-enhanced fluorescence. The use of silicon wafer for sandwich SERS immunoassay and aluminum foil for SEF in bacteria labeling with quantum dots were assessed. Perhaps the first application of silicon wafer for sandwich immunoassay resulted in an analyte limit of detection of 30 pM with a dynamic range of 0.03-4 nM. In comparison to gold film, it produced a signal intensity that was one order of magnitude lower, which was compensated for by a significantly lower standard deviation in the blank signal. The experiment on E.coli bacteria labeled with CdSeS/ZnS composite quantum dots yielded a high level of surface enhancement for all three substrates including uncommon aluminum foil and aluminum film. When the laser excitation source was changed, the results remained consistent, and there was a clear distinction between labeled and unlabeled cells. Overall, both silicon wafer and aluminum foil showed comparable results to conventional gold film and silver film substrates in different applications. Both of these substrates were found to be less expensive and produced more reproducible results than conventional substrates
Keywords: Novel Silicon; Type of access: Embargo; silicon wafer; aluminum foil